Az üzleti hálózatok és a klaszterek matematikai vizsgálatának lehetőségei - Lukács, Amarilla (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
My goal with this survey is to discover the opportunities of business networks' and clusters' mathematical examination. Nowadays it can be experienced that more and more countries use business networks and regional clusters as important tools to the development of the economy on the national and on the regional level too because they contribute to the enhancement of competitiveness. To the successful cluster-development policy it is essen-tial, that the clusters get organized in those industrial branches, which play a determining role in an area's life and which can be considered as a key sector in the region. Confirming the identity of potential clusters needs exhaustive excursions which cover more projections of the economical structure in a region, and these audits lean on indices constituted with different mathematical methods, on analyses leaning on the statistical datas and on the qualitative case studies summarizing the experiences of development programs realized in foreign countries.